Msingi wa fasihi simulizi - King'ei, Kitula G.; Kisovi, Catherine N. M. (Nairobi : Kenya Literature Bureau, 2010)
On the fundamentals of oral literature.
Includes bibliographical references (p. 161-163).
In Swahili.
Keywords: Folk literature, Swahili; Oral tradition -- Africa; Swahili language -- Texts